ABS and PLA sub-terahertz absorbers for 3D-printing technology. (March 2020) - Dorozhkin, K V; Teterina, D D; Badin, A V; Moskalenko, V D
Abstract: The results of research of the dielectric properties of absorbers based on commercial composite plastics for 3D printing in the sub-terahertz frequency range are presented. Spectra of the complex dielectric constant of plastics based on acrylonitrile butadiene styrene and polylactide with the addition of carbon nanoparticles in the frequency range 115-258 GHz are shown. The calculated transmission, reflection, and absorption spectra for the layers of the adsorbent with a thickness of 0.5 to 2 mm are presented.